Targeted Chromatinization and Repression of HIV-1 Provirus Transcription with Repurposed CRISPR/Cas9 - Alex Olson; Binita Basukala; Seunghee Lee; Matthew Gagne; Wilson W. Wong; Andrew J. Henderson (Viruses, 2020)
The major barrier to HIV-1 cure is the persistence of latent provirus, which is not eradicated by antiretroviral therapy. The “shock and kill” approach entails stimulating viral production with latency-reversing agents followed by the killing of cells actively producing the virus by immune clearance. However, this approach does not induce all intact proviruses, leaving a residual reservoir. CRISPR/Cas9 has been utilized to excise integrated Human Immunodeficiency Virus (HIV) DNA from infected cells in an RNA-guided, sequence-specific manner. Here, we seek to epigenetically silence the proviral DNA by introducing nuclease-deficient disabled Cas9 (dCas9) coupled with a transcriptional repressor domain derived from Kruppel-associated box (KRAB). We show that specific guide RNAs (gRNAs) and dCas9-KRAB repress HIV-1 transcription and reactivation of latent HIV-1 provirus. This repression is correlated with chromatin changes, including decreased H3 histone acetylation and increased histone H3 lysine 9 trimethylation, histone marks that are associated with transcriptional repression. dCas9-KRAB-mediated inhibition of HIV-1 transcription suggests that CRISPR can be engineered as a tool for block-and-lock strategies.